Macromarketing Vol.2 A global focus marketing systems, societal development, equity and poverty - Tadajewski, Mark (Ed); Shapiro, Stanley J.(Ed); Shapiro, Stanley J.(Ed) (Los Angeles SAGE Publications, 2009)
Society's impact on markets and marketing systems